Relationship of melatonin and serotonin levels with clinical neurological data in patients with cerebral ischemic hemispheric stroke during the early recovery stage of disease - Medvedkova, S. O. (Zaporozhye Medical Journal, 2017)
The aim of the research is the improvement of diagnostic measures in patients with cerebral ischemic hemispheric stroke (CIHS) on the basis of melatonin and serotonin plasma levels study in relation with evidence of neurologic impairment, level of functional independence, level of disability and their dynamics during the early recovery period of the disease. Materials and Methods. The complex clinical and paraclinical study of 77 patients (the average age 57,9±0,9 years) was done in the early recovery period of the CIHS. The study of all patients was complex clinic and paraclinical: test according to National Institute of Health Stroke Scale (NIHSS), Barthel Index (BI), modified Rankin Scale (mRS) was done on the 10th, 30th, 90th and 180th day of the disease; computer tomography of cerebrum was made on the first day of the disease; melatonin serum concentration and serotonin plasma level were determined on the 10th and 30th day from the onset of the CIHS. The melatonin/serotonin ratio (MSR = melatonin serum concentration / serotonin plasma level) was also calculated. Results and Discussion. Statistical reliable relations between the following indications have been identified: «serotonin plasma level on the10th day - dynamics mRS score on the 30-90th day» (R=+0,37, p˂0,05), «melatonin serum concentration on the10th day - dynamics mRS score on the 30-90th day» (R=-0,23, p˂0,05),«MSR on the 10th day - dynamics mRS score on the 30-90th day» (R=-0,40, p˂0,05),«serotonin plasma level on the 30th day - BI score on the 90th day»(R=+0,38, p˂0,05),«serotonin plasma level on the 30th - BI score on the180th day»(R=+0,40, p˂0,05), «MSR on the 30th day - NIHSS score on the 180th day» (R=+0,29, p˂0,05), «MSR on the 30th day - mRS score on the 90th day» (R=+0,29, p˂0,05), «MSR on the 30th day - mRS score on the 180th day» (R=+0,32, p˂0,05), «MSR on the 30th day - BI score on the 90th day» (R=-0,42, p˂0,05), «MSR on the 30th day - BI score on the 180th day» (R=-0,32, p˂0,05). Conclusions. The serum concentration of melatonin on the 10th day of CIHS correlates with the dynamics of points according to the modified Rankin Scale (mRS) on the 90th day (R=+0.37, p˂0.05); MSR is associated with BI on the 90th day (R=-0.42, p˂0.05) and 180th day of the disease (R=-0,32, p˂0,05); the serotonin plasma level on the 30th day of CIHS is associated with BI on the 90th day (R=+0,38, p˂0,05) and 180th day of the disease (R=+0.40, p˂0.05).